Occurrences of low-stress drop earthquakes in the eastern Ladakh-Karakoram zone of the Trans Himalaya and their tectonic implications - Paul, Arpita; Hazarika, Devajit (Journal of Asian Earth Sciences: X, 2022)
•Source parameters are computed for local earthquakes of the Ladakh-Karakoram zone.•The study reveals a low-stress drop ranging from ∼ 0.06 to 64.36 bar in the region.•Aseismic creeping patches in Karakoram Fault create low-stress drop earthquakes.•A partial stress drop mechanism is proposed for low-stress drop in forearc region.•Scaling relations between source parameters are reported for the region. The Ladakh-Karakoram zone is a unique testing ground for understanding the geodynamic evolution of the Himalaya-Karakoram orogeny. Despite the accumulation of a large amount of strain energy that originated due to the India-Asia collision along the Karakoram fault, earthquakes of M ≥ 7.0 are considerably less in the Karakoram Fault Zone (LKZ) compared to the Himalayan seismic belt in the northwest Himalaya. The spectral analysis of microearthquakes data (1.9 < ML < 4.3) recorded during 2009–2012 by 10 seismological stations of the LKZ reveals that the region produces low-stress drop earthquakes. Analysis of selected 51 earthquakes shows the seismic moment (Mo) within the range of 1.2 × 1012–4.3 × 1015 Nm with stress drop values varying from ∼ 0.06 to 64.36 bar. The low stress-drop earthquakes have significant implications in understanding seismogenesis. The earthquake cluster near the Tso-Morari Crystallines is associated with the brittle shear failure on the faults (e.g. Zildat, and Karzok Faults), and the low-stress drop of the earthquakes are explained by the partial stress drop model. The low effective fault strength due to fault weakening mechanisms in the studied segment of the Karakoram Fault zone promotes aseismic creeping patches producing low-stress drop earthquakes at the expense of generating large earthquakes. This study provides the scaling relations between important source parameters for the first time in the region which can serve as useful inputs for the assessment of earthquake hazards.